Conceptualization of "Taking the Essence" (bcud len) as Tantric Rituals in the Writings of Sangye Gyatso: A Tradition or Interpretation? - Chui, Tony (Religions, 2019)
Chülen (bcud len), the practice of "taking the essence", is an important practice within the Tibetan medical tradition. Through nourishing the body with the so-called depleted "essence", not only can one extend their lifespan but the practitioner can also restore their physical vitality. In recent years, this practice seems to be shifting away from the traditional religious mode of chülen involving tantric practices and rituals. Among the Tibetan medical literature, chülen is much emphasized in its religious aspects in the two important 17th century Tibetan medical commentaries on the Four Tantras (Rgyud bzhi) by the regent of the Fifth Dalai Lama, Desi Sangye Gyatso (Sde srid sangs rgyas rgya mtsho, 1653-1705): the Blue Beryl (Vaiḍūrya sngon po) and the Extended Commentary on the Instructional Tantra of the Four Tantras (Man ngag lhan thabs). Both texts are considered to be the most significant commentaries to the Four Tantras and have exerted a momentous impact on the interpretation of the Four Tantras even up to recent times. In their chapters on chülen, an assortment of chülen practices can be found. While there are some methods solely involving the extraction of essence in the material sense, there are also some in the spiritual-alchemical sense which are not observed in the Four Tantras. In this paper, I focus on the elaboration of the Four Tantras by Sangye Gyatso via his portrayal of ritualistic chülen in his two commentaries, where the tantric mode of promoting longevity and rekindling vitality is made efficacious by the operative socio-religious factors of his era, and which still exert their effect on our perception of chülen today.